The Important Role of Covalent Anchor Positions in Tuning Catalytic Properties of a Rationally Designed MnSalen-Containing Metalloenzyme - Garner, Dewain K.; Liang, Lei; Barrios, David A.; Zhang, Jun-Long; Lu, Yi (ACS Catalysis, 2011)
Two questions important to the success in metalloenzyme design are how to attach or anchor metal cofactors inside protein scaffolds and in what way such positioning affects enzymatic properties. We have previously reported a dual anchoring method to position a nonnative cofactor, MnSalen (1), inside the heme cavity of apo sperm whale myoglobin (Mb) and showed that the dual anchoring can increase both the activity and enantioselectivity over single anchoring methods, making this artificial enzyme an ideal system to address the above questions. Here, we report systematic investigations of the effect of different covalent attachment or anchoring positions on reactivity and selectivity of sulfoxidation by the MnSalen-containing Mb enzymes. We have found that changing the left anchor from Y103C to T39C has an almost identical effect of increasing rate by 1.8-fold and increasing selectivity by +15% for S, whether the right anchor is L72C or S108C. At the same time, regardless of the identity of the left anchor, changing the right anchor from S108C to L72C increases the rate by 4-fold and selectivity by +66%. The right anchor site was observed to have a greater influence than the left anchor site on the reactivity and selectivity in sulfoxidation of a wide scope of other ortho-, meta- and para-substituted substrates. The 1 . Mb(T39C/L72C) showed the highest reactivity (TON up to 2.32 min(-1)) and selectivity (ee % up to 83%) among the different anchoring positions examined. Molecular dynamic simulations indicate that these changes in reactivity and selectivity may be due to the steric effects of the linker arms inside the protein cavity. These results indicate that small differences in the anchor positions can result in significant changes in reactivity and enantioselectivity, probably through steric interactions with substrates when they enter the substrate-binding pocket, and that the effects of right and left anchor positions are independent and additive in nature. The finding that the anchoring arms can influence both the positioning of the cofactor and steric control of substrate entrance will help design better functional metalloenzymes with predicted catalytic activity and selectivity. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000294704500013&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Chemistry, Physical SCI(E) EI 19 ARTICLE 9 1083-1089 1